A Rare Heterozygous TINF2 Deletional Frameshift Mutation in a Chinese Pedigree With a Spectrum of TBDs Phenotypes - Ren, Hai-Long; Zheng, Ying-Chun; He, Guo-Qian; Gao, Ju; Guo, Xia (Frontiers in Genetics, 2022)
Telomere biology disorders (TBDs) caused by TINF2 mutations clinically present with a spectrum of phenotypes, from silent carriers to a set of overlapping conditions. A rare TINF2 frameshift mutation (c.591delG) encoding a truncated mutant TIN2 protein (pW198fs) was identified in a 6-year-and-3-month-old Chinese girl with neuroblastoma (NB) by next generation sequencing and confirmed by Sanger sequencing. To explore the possible implications of TINF2 mutations in TBDs development, the TINF2 mutant was transfected into human embryonic kidney (HEK) 293T cells, and mRNA expression of the shelterin complex components and the cellular distribution of mutant TIN2 were examined. The TINF2 mutation was phenotypically associated with short stature in the proband, nail dystrophy and spotted hypopigmentation in her mother, and psoriasis in her older brother. I-TASSER modeling analysis revealed conformational changes of the mutant TIN2 protein and loss of pivotal domains downstream of the 198th amino acid. Additionally, mRNA expression of the shelterin components was downregulated, and TIN2 mutant protein expression was reduced in HEK293T cells transfected with mutant TINF2. Furthermore, instead of nuclear localization, the mutant TIN2 was distributed in both the cytoplasm and the nucleus. The TINF2 gene mutation might adversely impact the functionality of the shelterin complex and the telomere maintenance mechanism and involved in TBDs development. TBDs have been associated with increased cancer risk. To the best of our knowledge, this is the first report of NB in patients with TBDs. The relationship between the TINF2 mutation and NB may need to further study.